Physiological responses of some local cowpea from Southwest Maluku (Indonesia) varieties to drought stress (Biodiversitas Journal of Biological Diversity, 2017)
Karuwal Rl, Suharsono, Tjahjoleksono A, Hanif N. 2017. Physiological responses of some local cowpea from Southwest Maluku (Indonesia) varieties to drought stress. Biodiversitas 18: 1294-1299. The aim of this study was to analyze the physiological responses of some local cowpea from Southwest Maluku (Indonesia) varieties to drought stress. The physiological responses were analyzed by measuring plant height, number of leaves, relative water content (RWC), and chlorophyll content using Anova and were continued with Duncan test at 5% significance level. Results of this research showed that the varieties and drought stress in the form of watering periods to affect to all variables except plant height. Physiological responses showed that at every ten days watering periods, the crimson varieties gives the highest plant height (33.85 cm), the brown varieties gives the highest number of leaves (30), the dark brown varieties have the highest RWC (88.675%), and the highest content of chlorophyll a (0.5088 mg/L), chlorophyll b (1.595 mg/L), and total chlorophyll (1.5095 mg/L) are found in white varieties. The supply of water at every ten days is the optimum time of drought stress in cowpea. Further research will be needed on the responses of the other variables for screening, selection, then multi-location trials to obtain tolerant local cowpea varieties to drought.
Keywords: Cowpea; drought stress; physiological responses